A Comparative Study between Physical Properties of Compact and Ring Yarn Fabrics Produced from Medium and Coarser Yarn Counts. (23rd November 2014) - Abou-Nassif, Ghada Ali
Abstract : In compact spinning, fibers in drawing stage are condensed using air suction, which results in the produced yarns which significantly differ from ring spun yarns in their physical and mechanical properties. This study compares between physical properties of compact and ring yarn fabrics woven from coarser and medium yarn counts. The experimental results were statistically analyzed using ANOVA. The findings of this study revealed that woven fabrics produced from compact spun yarns are superior to those produced from ring spun yarns with respect to breaking strength, breaking elongation, abrasion resistance, tearing strength, and air permeability.